The Effectiveness of Tourism Object Development by Regionally Owned Enterprises (BUMDER) in Community Empowerment: A Case Study of Brintik Village, Klaten Regency - Santoso, Ary Adi; Syaifudin (GoAcademica Research & Publishing, 2025)
This study aims to evaluate the effectiveness of the development of Regionally- Owned Enterprises (BUMDER) at the Umbul Brintik tourist attraction along with supporting and inhibiting factors in community empowerment in Malangjiwan Village. The theory used is Duncan's effectiveness theory in Steers (1985). The research method uses a descriptive qualitative research method. The results of the study indicate that the development of Regionally-Owned Enterprises (BUMDER) at the Umbul Brintik tourist attraction in community empowerment in Malangjiwan Village on the indicator of achieving goals is considered effective, seen during the period 2017-2025, concrete target targets can be achieved which have a positive impact on the receipt of Regional Original Income and economic benefits for Malangjiwan villagers. The integration indicator is considered effective because socialization has been carried out through Village Deliberations every three months and Village Discussions once a year. The adaptation indicator is considered quite effective because the development of Umbul Brintik as a therapeutic tour can hold an educational scholarship program for Malangjiwan villagers. However, it is necessary to improve the digital capabilities of the Promotion Team and develop a technology-based system that is integrated with the digital cashier system. Supporting factors include the existence of concrete targets that have been achieved to contribute to financing village development and economic benefits for villagers and MSME actors in Malangjiwan Village, while inhibiting factors include the lack of digital training for the Promotion Team and a digital system that has not been integrated in developing the Umbul Brintik tourist attraction. The development of the Umbul Birntik tourist attraction will be highly effective if it is strengthened by the public accountability needed to assess the accountability and openness of information from the Malangjiwan Village Government and BUMDER Sumber Makmur to villagers by involving relevant stakeholders in Malangjiwan Village.